Controls on Water Storage and Drainage in Crevasses on the Greenland Ice Sheet. Issue 9 (6th September 2021) - Chudley, T. R.; Christoffersen, P.; Doyle, S. H.; Dowling, T. P. F.; Law, R.; Schoonman, C. M.; Bougamont, M.; Hubbard, B.
Abstract: Surface crevasses on the Greenland Ice Sheet (GrIS) capture nearly half of the seasonal runoff, yet their role in transferring meltwater to the bed has received little attention relative to that of supraglacial lakes and moulins. Here, we present observations of crevasse ponding and investigate controls on their hydrological behavior at a fast‐moving, marine‐terminating sector of the GrIS. We map surface meltwater, crevasses, and surface‐parallel stress across a ∼2, 700 km 2 region using satellite data and contemporaneous uncrewed aerial vehicle (UAV) surveys. From 2017 to 2019 an average of 26% of the crevassed area exhibited ponding at locations that remained persistent between years despite rapid advection. We find that the spatial distribution of ponded crevasses does not relate to previously proposed controls on the distribution of supraglacial lakes (elevation and topography) or crevasses (von Mises stress thresholds), suggesting the operation of some other physical control(s). Ponded crevasse fields were preferentially located in regions of compressive surface‐parallel mean stress, which we interpret to result from the hydraulic isolation of these systems. This contrasts with unponded crevasse fields, which we suggest are readily able to transport meltwater into the wider supraglacial and englacial network. UAV observations show that ponded crevasses can drain episodically and rapidly, likely through hydrofracture. We therefore propose that the surface stress regime influences a spatially heterogeneous transfer of meltwater through crevasses to the bed of ice sheets, with consequences for processes, such as subglacial drainage and the heating of ice via latent heat release by refreezing meltwater. Plain Language Summary: Surface crevasses on the Greenland Ice Sheet (GrIS) transfer nearly half of all the ice sheet's meltwater to the bed, yet when, where, and how this occurs is poorly understood. We use large‐scale satellite analysis and uncrewed aerial vehicle (UAV) surveys to assess the spatial variability of meltwater ponding in crevasses across a fast‐flowing sector of the western GrIS. Between 2017 and 2019 an average of a quarter of crevasse fields ponded, in roughly the same area every year. However, the locations of such ponding cannot be explained in the same way as supraglacial lakes, which collect in surface basins. Instead, we find that ponded crevasses exist in regions of compressive surface stress. We suggest that this is because compressive regimes close pathways that elsewhere allow crevasses to drain into the wider surface hydrological system. Using UAV surveys, we show that these ponded crevasses instead drain rapidly to the bed by hydrofracture. Differing drainage processes in regions of compressive and extensional regimes may have distinct consequences for subglacial drainage and the heating of the ice sheet due to energy release during meltwater refreezing. Key Points: At a marine‐terminating sector of the Greenland Ice Sheet, 26% of all crevasses ponded between 2017 and 2019; the rest remained unfilled Ponded crevasse locations persist between years but, unlike supraglacial lakes, this distribution is not topographically controlled Crevasses pond in compressive stress regimes, likely due to hydraulic isolation by creep closure, and drain predominantly via hydrofracture